The Effect of Giving Kajah Pudding (Cardamom Ginger) on Reducing the Frequency of Nausea and Vomiting in First Trimester Pregnant Women in the Medan Tuntungan Health Center Working Area in 2023 - Jani Puspita Sari, Ayu; Damanik, Rini Astuti; Gultom, Yohana Tetty (Jurnal EduHealth, 2023)
Nausea and vomiting occur in 60-80% of primigravida and 40-60% in multigravida. Hormonal changes in each pregnant woman will give a different response, so not all experience nausea and vomiting in pregnancy. The purpose of this study was to analyze the effect of giving Kajah (Cardamom Ginger) pudding on reducing the frequency of nausea and vomiting in first trimester pregnant women. This research method uses pre-experiment with pre test and post test group design. The sample of this study were 16 pregnant women TM I. The sampling technique used purposive sampling technique. Data analysis using paired sample t-test statistics. The results showed that the frequency of nausea and vomiting of respondents before being given Kajah pudding (Cardamom Ginger) the majority was in the medium category of 10 pregnant women (62.6%). After being given Kajah (Cardamom Ginger) pudding, the frequency of nausea and vomiting was mostly in the mild category as many as 11 pregnant women (68.8%). Based on the paired t test, the sig value or P value is 0.000 which shows less than 0.05 (0.000 <0.05). The conclusion of this study is that there is an effect of giving Kajah Pudding (Cardamom Ginger) on reducing the frequency of nausea and vomiting in first trimester pregnant women in the Medan Tuntungan Health Center Working Area in 2023.